Modern Indices for International Economic Diplomacy - Charles, Vincent; Emrouznejad, Ali. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Composite indices are used by national and international organisations, as well as governments and corporations, to track various performance aspects of a country's economy and its people, evaluate progress, and engage constructively in policy dialogue; and they have long proven useful as communication tools and inputs into decision-making and policymaking. Modern Indices for International Economic Diplomacy compiles a spectrum of relevant indices for development and well-being used in benchmarking across nations, namely the OECD Better Life Index, the Gini Index, the Gender Equality/Inequality Index, the International Energy Security Risk Index, the Big Mac Index, the Country Risk Index, the Corruption Perceptions Index, and the Global Terrorism Index. The book will be relevant to practitioners, policymakers, researchers, and students interested in the topic of international economic relationships. Vincent Charles is a Professor and Director of the Center for Value Chain Innovation at CENTRUM Católica Graduate Business School, Pontifical Catholic University of Peru, Lima, Peru. Ali Emrouznejad is a Professor and Chair in Business Analytics at Surrey Business School, The University of Surrey, UK.
Chapter 1. Introduction -- Chapter 2. Regional Competitiveness Index (UFR) -- Chapter 3. Doing Business Index (UFR) -- Chapter 4. Social Progress Index (UFR) -- Chapter 5. Country Risk Index -- Chapter 6. Corruption Perception Index (UFR) -- Chapter 7. Happiness Index (UFR) -- Chapter 8. World Competitiveness Index (UFR) -- Chapter 9. Global Marketing Index (UFR) -- Chapter 10. Human Development Index -- Chapter 11. Index of Economic Freedom -- Chapter 12. GINI Index -- Chapter 13. Democracy Index -- Chapter 14. Big Mac Index (UFR) -- Chapter 15. Global Entrepreneurship Index.
Keywords: International economic relations; Economics; International business enterprises; Business enterprises-Finance.; Economic development; Macroeconomics; International Economics; Economics; International Business; Corporate Finance; Economic Growth; Macroeconomics and Monetary Economics